|
>> . 10-11 . |
2.
2.4. .
-, . . : I = ƒ(φ1 - φ2). - . , . - . ( ) 1826 ., .
20- . XIX . , ( , , ), , , . , . *, . , . * E , , , , . , , , . 1826 . . . . 23 . 1849 . .
2.12 1, 2. . ( ) U = φ1 φ2, φ1 1 ( ), φ2 2 ( ). φ1 > φ2, U > 0 1 2, . , I (I > 0). : I ~ U. (2.4.1) , () . (2.4.1) I = G(φ1 - φ2) = GU. (2.4.2) . G , . . . , , ; . : ( ) . ,
. , . , . G (2.4.2) :
(2.4.3) : . , (2.4.3) (2.4.2) , *. , . , , . , 1.21, : . , . . , : . , , , , . , , . . * , , 2.15. , . . , . ( ) . . . . . (2.4.3):
.
|
|
|